Designing decentralized small-scale bioenergy systems based on short rotation coppice for rural poverty alleviation - Da Silva, Izael (My University, 2015)
Access to electricity is crucial for the attainment of the Millennium Development Goals of poverty reduction and environmental sustainability. In East Africa, increasing environmental degradation and modern energy supply are a major obstacle to sustainable rural development. Small-scale bioenergy systems can supply clean, renewable and affordable energy to rural communities while at the same time creating new job opportunities and having beneficial impacts on natural resources especially when fed from Short Rotation Coppice (SRC). However, bioenergy systems are complex because their three components feedstock supply, conversion technology and energy allocation are influenced by environmental factors simultaneously with economic and social factors. Assessing these factors and their interdependence is essential to determine the project’s contribution to sustainable development as failure of one component can lead to failure of the entire system. Decision Support Tools (DST) structure the collection and evaluation of quantitative and qualitative information about social, economic and environmental impacts at scales ranging from local to national level. DSTs enable transparent and informed decisions even when limited information is available and many participants with different expertise and interests are involved to consider all relevant criteria. This paper introduces an approach to develop a DST assessing sustainability of bioenergy systems.
Keywords: bio-energy management; developing countries; decision support tools